The influence of sports on proactive personality and academic achievement of college students: The role of self-efficacy - Li, Xinnan; Liu, Min; Yu, Haofei; Zhang, Zhanjia; He, Zhonghui (Frontiers in Psychology, 2022)
Objective To explore the mediating effect of self-efficacy on the relationship between the proactive personality and academic performance of college students in different sports groups. Methods A questionnaire survey is used to study 552 college students. The research tools include the proactive personality scale, the self-efficacy scale table (general, academic, and self-regulation efficacy scale tables), and the academic performance self-report scale table. This research employs SPSS 11.0 statistical software to carry out correlation analysis, regression analysis, and t-tests on the data collected, while the test of mediating effect is carried out by AMOS 22.0. Results (1) The degree of self-efficacy and academic performance of college students participating in physical activities is significantly greater than that of the non-sports group; (2) the proactive personality level of the sports group is significantly higher than the non-sports group in the dimension of “conscientiousness”; (3) a confirmatory factor analysis of the mediating effect hypothesis model, using the structural equation model, found that self-efficacy plays a full mediating role in the relationship between proactive personality and academic performance; the direct effect of self-efficacy on the proactive personality and academic performance of college students in different sports groups is not significant. Conclusion College students involved in sports exercise have higher scores on some items about proactive personality than non-sports groups; girls’ self-efficacy level is higher than that of boys; self-efficacy plays a full mediating role in the relationship between proactive personality and academic performance; self-efficacy had no significant effect on proactive personality and gender in different sports groups.